Hubungan Tingkat Pengetahuan dan Usia Ibu Saat Hamil dengan Status Gizi pada Balita di UPTD Puskesmas Panarung Palangka Raya - Olvi Eka Kaharap; Karmitasari Yanra Katimenta; Nia Pristina (The Journal General Health and Pharmaceutical Sciences Research, 2025)
The incidence of short toddlers or commonly called stunting is one of the nutritional problems experienced by toddlers in the world today. Stunting is a chronic condition in toddlers that describes inhibited body growth due to nutritional deficiencies in the long term. Stunting can have a bad impact on a person both in the short and long term. The adverse impact in the short term is disruption of brain development, intelligence, physical growth disorders, and metabolic disorders in the body. Meanwhile, the long-term adverse effects are decreased cognitive ability and learning achievement, decreased immunity, and a high risk of diabetes, obesity, heart and vascular disease, cancer, stroke, and disability in old age. Objective: To analyze the corellation between the level of knowledge and the incidence of stunting in toddlers at the UPTD Panarung Palangka Raya Health Center and to analyze the relationship between the age of the mother during pregnancy and the incidence of stunting in toddlers at the UPTD Panarung Health Center Palangka Raya. Methods: The design of this study is correlational (Non-Experimental), a type of cross sectional approach; the sample is 59 respondents at the UPTD Panarung Health Center. Results: Based on the results of the Spearman Rank statistical test, a value of p 0.000 < 0.05 can be concluded that H1 is accepted, meaning that there is a meaningful corellation between maternal knowledge and stunting incidence. And the results of the Spearman Rank statistical test obtained a value of p 0.009 < 0.05, it can be concluded that H1 is accepted, meaning that there is a meaningful corellation between the mother's age and the incidence of stunting. Conclusion: The results of this study show that there is a corellation between the level of awareness and the incidence of stunting in toddlers. And there is a corellation between the age of the mother during pregnancy and the incidence of stunting in toddlers.